2012
DOI: 10.1111/j.1365-2648.2012.06053.x
|View full text |Cite
|
Sign up to set email alerts
|

Leadership facilitation strategies to establish evidence‐based practice in an acute care hospital

Abstract: Successful key strategies were evidence-based practice education and establishing internal opportunities to disseminate findings. Transformational nursing leadership drives organizational change and provides vision, human and financial resources and time that empowers nurses to include evidence in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 25 publications
3
78
1
17
Order By: Relevance
“…Although Hauck, Winsett and Kuric's [46] work focused on transformational leadership to achieve organizational change pertaining to evidence-based practice (EBP), lessons learned in their study are applicable in addressing the issues the participants in this study reported. For example, they suggest that for change to be successfully implemented, a broad vision of the structure and processes need to be in place.…”
Section: Discussionmentioning
confidence: 96%
“…Although Hauck, Winsett and Kuric's [46] work focused on transformational leadership to achieve organizational change pertaining to evidence-based practice (EBP), lessons learned in their study are applicable in addressing the issues the participants in this study reported. For example, they suggest that for change to be successfully implemented, a broad vision of the structure and processes need to be in place.…”
Section: Discussionmentioning
confidence: 96%
“…Las estrategias claves de éxito son la educación y el establecimiento de oportunidades internas para difundir los resultados; la transformación del liderazgo del personal de enfermería impulsa el cambio organizacional y proporciona la visión, los recursos y el tiempo favoreciendo la gestión administrativa y financiera de la instituciones (26).…”
Section: Liderazgo Como Competencia De Los Trabajadores Y Concepción unclassified
“…1 The results presented refer to a detail of phase 1 of the Rogers' theory: the phase of knowledge. 9 An intentional sample, consisting of all the nurses managers of the Unidades de Internação do Hospital Público de Ensino (UI-HPE -Inpatient Units of the Public Teaching Hospital) (n = 18), was composed, excluding those on vacation or leave. A questionnaire was applied for socio-demographic characterization of the participants (elaborated by the authors), and the details of this intervention are presented in recent publications.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 The engagement of Nursing coordination, as indicated by contemporary scientific productions, presents as a crucial strategy to make the hospital context favorable to EBP. This is due to the fact that the Nursing leaders present themselves capable of encouraging and supporting the assistance teams in the change of practices -an organizational change, therefore, 8,9 provides the undertaking of strategies that increase the cooperation and engagement of the workers as important elements for the implementation of EBP -in particular to avoid discontinuance of this practice in the organization. 1,8,9 In this perspective, the Rogers Innovations Diffusion theory 10 has been undertaken to achieve leadership engagement and induction of hospital organizational culture in favor of EBP implementation among nurses.…”
Section: -3mentioning
confidence: 99%